ANALYSIS OF LOVE SCAM: CASE STUDY OF SEXTORTION INVOLVING A MEMBER OF THE MEDAN DPRD - Senonugroho, Handy (Program Studi Sosiologi Universitas Malikussaleh, 2024)
The rapid advancement of communication technology has brought about significant changes in societal interactions, but it has also amplified the threat of cybercrimes, including love scams and sextortion. This article explores cases of sextortion involving a convict and a member of a regional legislative council, while delineating the cyberculture and space transition factors that facilitate these crimes. Furthermore, the article adopts a qualitative approach with case study method and literature study to comprehend the phenomena of love scams, sextortion, and related cases. Policing strategies for tackling sextortion are presented, with an emphasis on e-policing. Conclusions and recommendations for effectively combating sextortion are also discussed, including the importance of prevention, the utilization of technology, and a focus on victim recovery. The article proposes a collaborative effort to address this issue comprehensively.